Simulation with Arena - Kelton, W. David (McGraw-Hill Education, 2015)
Includes bibliographical references (pages 615-617) and index.; This book provide an introduction to simulation using Arena. It is intended as an entry-level simulation text, most likely in a first course on simulation at the undergraduate or beginning graduate level.